1995
DOI: 10.1523/jneurosci.15-05-03328.1995
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and targeting of a mu-opioid receptor (MOR1) in brain and spinal cord

Abstract: Opioid receptors regulate neuronal activity by both pre- and postsynaptic mechanisms. We recently reported that the cloned delta- opioid receptor (DOR1) is primarily targeted to axons, suggesting a presynaptic role. In the present study we have studied the distribution and targeting of another opioid receptor, the mu-opioid receptor (MOR1), by raising anti-peptide antisera to the C-terminal peptide of MOR1. The specificity of the antisera was determined by analysis of transfected cells, Western blots, and immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

76
390
3
5

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 588 publications
(474 citation statements)
references
References 0 publications
76
390
3
5
Order By: Relevance
“…The Mr's of the MORs in the mouse and rat CPu detected with anti-μC are similar to those detected by [ 3 H]β-funaltrexamine labeling [18] or an antiserum against a 15-aa peptide corresponding to amino acid 384-398 predicted from cloned rat MOR-1 [5], for which the whole brains were used. In addition, the Mr of the MOR in the rat thalamus in this study is consistent with that detected by receptor phosphorylation [23].…”
Section: Affinity-purified Rabbit Polyclonal Anti-mor Antibody Anti-mentioning
confidence: 53%
See 1 more Smart Citation
“…The Mr's of the MORs in the mouse and rat CPu detected with anti-μC are similar to those detected by [ 3 H]β-funaltrexamine labeling [18] or an antiserum against a 15-aa peptide corresponding to amino acid 384-398 predicted from cloned rat MOR-1 [5], for which the whole brains were used. In addition, the Mr of the MOR in the rat thalamus in this study is consistent with that detected by receptor phosphorylation [23].…”
Section: Affinity-purified Rabbit Polyclonal Anti-mor Antibody Anti-mentioning
confidence: 53%
“…Morphine acts primarily on the MOR [3] and are among the most widely abused drugs. MOR is widely distributed in neurons throughout the brain and spinal cord [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The small population of neurons coexpressing SPR and MORs also makes the formation of heterodimers between these two receptors less likely (37). Anatomical studies illustrate that SPRs are located primarily on the somato-dendritic surfaces of neurons (i.e., postsynaptically), whereas MORs are found both postsynaptically and on axonal components (i.e., presynaptically) (38). ESP7 may, by causing release of chemical mediators from SPR-expressing neurons, be indirectly activating secondary messengers systems within MORexpressing neurons to alter the development of tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-MOR antibody was a rabbit antiserum raised against amino acids 384-398 of the cloned rat MOR-1 (DiaSorin, Stillwater, MN, catalog no. 24216), which has been characterized (Arvidsson et al, 1995) and shown to label dorsal horn neurons (Spike et al, 2002). Pre-absorption of the MOR antibody with its immunizing peptide (10 µg/ml) abolished the staining.…”
Section: Immunohistochemistrymentioning
confidence: 99%